SISTEM INFORMASI PENDATAAN BEASISWA KURANG MAMPU DENGAN PARAMETER PENGHASILAN ORANG TUA DAN KONDISI RUMAH DI SMPN 1 KAB. TEBO: Scholarship;Information;Junior High School;Web;Management. - Elzas; Rahmatina, Masayu (JURNAL AKADEMIKA, 2022)
The aim of the research is to create an information system for processing under privileged scholarships to produce faster, more precise, accurate and useful data for SMPN 1 Tebo Regency. Input Needs Data entry consists of input requirements at SMP Negeri 1 Tebo Regency, namely data on prospective scholarship recipients, data on criteria for determining scholarship recipients, and reports in SMP Negeri 1 Tebo Regency. Process Needs Process requirements needed in SMP Negeri 1 Tebo Regency have several parts, namely the process of data on prospective scholarship recipients, data processing of criteria for determining scholarship recipients, recap data processing and the process of printing scholarship recipient reports. Output Needs Expenditure data generated is in the form of information that will be displayed, including scholarship recipient reports. The scholarship data collection system that runs at SMPN 1 Kab. Tebo still has a few short comings where the admin must be careful in inputting data. With this designed system, it provides easy delivery of information to SMPN 1 Kab.